1990
DOI: 10.1055/s-2007-1004959
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Injections of GHRH in Normal Children and Adults

Abstract: Sir, Dr. Hummelink and Sippel have described in detail their studies on repetitive injections of growth hormone releasing hormone to normal volunteers and patients with growth hormone deficiency (Hummelink and Sippel 1990). We would like to add our comments to the effects of repetitive injections of GHRH-44 in normal adults. The subjects in the study of Hummelink and Sippel, with an average age (± SD) of 25.3 ± 4.4 years, showed persistent elevated GH responses to repeated GHRH administration at two hours inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
2
1
Order By: Relevance
“…In part at variance with the present findings are the results of studies performed in adult subjects in whom GHRH administration was found to inhibit the GH response to the second GHRH bolus (2). This phenome¬ non has been explained by an increase in the somatostatinergic tone secondary to GHRH administration, which antagonizes the action of the following GHRH challenge, but not that of the stimuli acting through inhibition of SRIH release such as arginine and pyridostigmine (5).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In part at variance with the present findings are the results of studies performed in adult subjects in whom GHRH administration was found to inhibit the GH response to the second GHRH bolus (2). This phenome¬ non has been explained by an increase in the somatostatinergic tone secondary to GHRH administration, which antagonizes the action of the following GHRH challenge, but not that of the stimuli acting through inhibition of SRIH release such as arginine and pyridostigmine (5).…”
Section: Discussioncontrasting
confidence: 71%
“…In the last few years, several authors have demonstrated that the plasma GH response of adult subjects to acute GHRH stimulation is abolished by a previous GHRH injection ( 1,2). It has been speculated that an increase in the somatostatinergic tone following the first GHRH challenge might be responsible for the pituitary lack of response to the second stimulus.…”
mentioning
confidence: 99%
“…The influence of adiposity on the neuroregulation of GH secretion in adults has been independently confirmed from the approximate entropy (ApEn) metric, which demonstrates greater irregularity of GH secretion in the obese, suggesting greater feedback activity within the axis [5][6][7]14]. In contrast, there are very few data on GH neuroregulation of overweight youth, and data from adults may not be directly applicable to youth because the neuroregulation of GH secretion likely differs in youth and adults [15,16].…”
Section: Introductionmentioning
confidence: 99%